Предмет: Математика, автор: msnastja1999

Упростить выражение (3/a^3-a + 1/a-1):9-a^2/a-1
ОЧЕНЬ НАДО,ПОЖАЛУЙСТА!

Приложения:

msnastja1999: a=log2 16 (2 маленькая)

Ответы

Автор ответа: maksimcat
1
( \frac{3}{a^2-a} + \frac{1}{a-1} ): \frac{9-a^2}{a-1} =( \frac{3}{a(a-1)} + \frac{1}{a-1} ): \frac{9-a^2}{a-1} = \\  \\  \frac{3+a}{a(a-1)} * \frac{a-1}{(3+a)(3-a)} =  \frac{1}{a(3-a)}  \\  \\ a= log_{2} 16=4 \\  \\   \frac{1}{a(3-a)}  =  \frac{1}{4(3-4)}  =- \frac{1}{4}  \\  \\
Похожие вопросы
Предмет: Геометрия, автор: lesya9042000